Efeitos da estimulação nervosa elétrica transcutânea na vascularização placentária de ratas com restrição induzida ao fluxo uterino. - Guimarães, Camila Souza de Oliveira (2008)
Introduction: Based on the high levels of fetal morbidity and mortality related to pregnancies complicated by placental insufficiency and intra uterine growth restriction, and based on studies using Transcutaneous Electrical Nerve Stimulation (TENS) as a treatment for placental insufficiency, the aim of this study was to evaluate the effect of TENS on fetal and placental development in pregnancies with restricted uteroplacental blood flow was experimentally induced by clamping the uterine artery. Material and Methods: In the study were included sixteen Wistar rats, submitted to uterine artery clamping surgery at day fifteen of pregnancy. Four were included in the group of animals with uterine artery clamping and submitted to TENS (CE), four in the group with clamp and without electrostimulation, four in the group in which a filament was passed around the uterine artery and stimulated (FE) and four in the group in which a filament and not stimulated. The surgery was performed on the 15th day of pregnancy, and the electrostimulation sessions were performed since the immediate postoperative until day nineteen of pregnancy, with duration of 30 minutes, one session per day. On day nineteen of pregnancy, animals were subjected to euthanasia, and fetuses and placentas were weighted and measured. To analyze the number of placental vessels, immunohistochemistry was performed with Factor VIII. Results: Cases with clamp presented a higher number of fetal reabsorptions (p=0.017). Fetal weight was smaller in cases with clamp (p<0.001) and stimulated (p=0.01). Fetal length was smaller in cases with clamp (p<0.001) and stimulated (p=0.002). Placental weight was smaller in cases with clamp (p<0.001) and stimulated (p<0.001). Placental volume was smaller in cases with clamp (p<0.001) and stimulared (p=0.016). Cases which were stimulated presented a smaller number of placental vessels (p<0.001), independent from procedure (p=0.828). There was a positive correlation between number of fetuses and reabsorptions (p=0.00444), between placental and fetal weights (p<0.001) and between number of placental vessels and number of fetuses in cases stimulated (p=0.0131). There was a negative correlation between fetal length and number of fetuses in cases stimulated (p=0.0150). Conclusions: Stimulus did not elevated the number of placental vessels and seems not to have a beneficial contribution to fetal and placental development in rats with uterine flow restriction. We suggest that TENS should be used cautiously during pregnancy, because its parameters of utilization may have harmful effects to intra-uterine development.